2015
DOI: 10.1016/j.envpol.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal colonization and growth of the hybrid larch F 1 under elevated CO 2 and O 3

Abstract: We studied the colonization of ectomycorrhizal fungi and species abundance of a hybrid larch (F1) under elevated CO₂ and O₃. Two-year-old seedlings were planted in an Open-Top-Chamber system with treatments: Control (O3 < 6 nmol/mol), O₃ (60 nmol/mol), CO₂ (600 μmol/mol), and CO2 + O₃. After two growing seasons, ectomycorrhiza (ECM) colonization and root biomass increased under elevated CO₂. Additionally, O₃ impaired ECM colonization and species richness, and reduced stem biomass. However, there was no clear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 65 publications
6
48
1
Order By: Relevance
“…These trends have suggested that Qs may have higher ability for the recover from O 3 damages and may be more tolerant to eO 3 than Qm under eCO 2 based on the summary made by Kohno et al (2005) and Yamaguchi et al (2011). No significant effects were observed in foliar P concentration at eO 3 for both species at the present study, which was in agreement with the results of Wang et al (2015). Although we hypothesized that leaf P would be increased under eCO 2 since the acquisition of P is strongly affected by physiological condition of host plants through the morphological and the physiological properties of rhizosphere (Adalsteinsson et al, 1994;Ruiz et al, 1996;Kayama et al, 2005;Kayama and Yamanaka, 2014;Wang et al, 2015), there was no difference in leaf P at eCO 2 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These trends have suggested that Qs may have higher ability for the recover from O 3 damages and may be more tolerant to eO 3 than Qm under eCO 2 based on the summary made by Kohno et al (2005) and Yamaguchi et al (2011). No significant effects were observed in foliar P concentration at eO 3 for both species at the present study, which was in agreement with the results of Wang et al (2015). Although we hypothesized that leaf P would be increased under eCO 2 since the acquisition of P is strongly affected by physiological condition of host plants through the morphological and the physiological properties of rhizosphere (Adalsteinsson et al, 1994;Ruiz et al, 1996;Kayama et al, 2005;Kayama and Yamanaka, 2014;Wang et al, 2015), there was no difference in leaf P at eCO 2 .…”
Section: Discussionsupporting
confidence: 83%
“…No significant effects were observed in foliar P concentration at eO 3 for both species at the present study, which was in agreement with the results of Wang et al (2015). Although we hypothesized that leaf P would be increased under eCO 2 since the acquisition of P is strongly affected by physiological condition of host plants through the morphological and the physiological properties of rhizosphere (Adalsteinsson et al, 1994;Ruiz et al, 1996;Kayama et al, 2005;Kayama and Yamanaka, 2014;Wang et al, 2015), there was no difference in leaf P at eCO 2 . This was also supported by Conroy (1992), indicating the view that eCO 2 increased the P demand of leaves.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Reduced C allocation to roots impairs mycorrhizal symbiosis, for instance, in birch (Kasurinen et al., 2005), hybrid aspen (Edwards & Zak, 2011), beech (Pritsch et al., 2009), hybrid larch (Wang et al., 2015), and blue wild rye ( Elymus glaucus ; Yoshida, Gamon, & Andersen, 2001). Mycorrhizae are ubiquitous in all terrestrial ecosystems and play an essential role in soil–plant nutrient exchange and via the turnover of external mycelium for the transfer of root‐derived C to SOM (Godbold et al., 2006).…”
Section: Changes In Soil Microbiota and Nutrient Cyclingmentioning
confidence: 99%
“…Moreover, the carbon (C) gain and allocation below ground are also increased. As an indirect result of these changes, the relationship of tree roots and symbionts is altered (Wang et al 2015b).…”
Section: Introductionmentioning
confidence: 99%